Breastfeeding-Prevent the Preventable - Gupta, Megha; Mehta, Sumita; Grover, Anshul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Breastfeeding is the best way of providing ideal food for growth and development of infants. There is urgent need for counselling of mothers in antenatal and postpartum period to promote effective breastfeeding practices. The aim of this study was to assess the knowledge, attitude and practices of breastfeeding among postnatal mothers admitted in inpatient department of obstetrics and gynaecology of Babu Jagjivan Ram Memorial hospital. Methods: 200 postnatal mothers were enrolled using random sampling method and data collection was done by face to face interview using structured questionnaire. Results: Most women (42.5%) belonged to age group (21-25 years), were multiparous (60.5%) and belonged to joint family. All of them were housewives, had vaginal delivery and belonged to lower socioeconomic status. Most women knew the importance of exclusive breastfeeding, early initiation, colostrum and feeding on demand. 16% women gave pre lacteal feed most common being honey. False cultural belief as discontinuing breastfeeding while being sick, and menstruating is still prevalent in the society. However according to 93% women breastfeeding decreases family expenses. Few women are still hesitant in breastfeeding in public places and find it as an interference to sexual life. Practices of breast feeding in the form of knowledge of proper attachment and latching techniques was found to be very poor in this study. Conclusions: Most mothers had good knowledge (49%), good attitude (76%) but only 5% women had good practices of breastfeeding.